Higher Education Internationalization and the Private Education Institutions in Brazil - Guazzelli, Maria Elisabete; Raymundo, Camila Sotello; Varjabedian, Deborah; Akerman, Marco (ABCS Health Sciences, 2015)
The implementation of new curriculum of health courses in private universities is a complex task. The pedagogical concepts in these institutions conform to the knowledge economy, being heavily influenced by the internationalization of education and the market designs becomes important in the vocational training from a qualitative point of view. This logic, growing between higher education institutions in Brazil, influences not only the principles of design and implementation of curricular models, but the pedagogical strategies, instruments, and relationships education population of teacher‑student‑institution. This article discusses some of the historical and contemporary aspects involved in designing the University in Brazil and some of the impacts determined by the internationalization of higher education. We note that in the process of internationalization of higher education, the Brazilian private university experience an asymmetrical relationship with the core countries, occupying a subordinate position, submitting to the decisions of transnational corporations.